Kemampuan Menulis Teks Percakapan Bahasa Makassar Siswa Kelas VIII SMP Negeri 5 Tompobulu Kabupaten Gowa - Ilham Ilham; Syamsudduha Syamsudduha; Aswati Asri (Panrita: Jurnal Bahasa dan Sastra Daerah serta Pembelajarannya, 2026)
This study aims to describe the ability to write Makassar language conversation texts of class VIII students of SMP Negeri 5 Tompobulu, Gowa Regency. This study is a quantitative descriptive study. The population in this study was class VIII of SMP Negeri 5 Tompobulu, Gowa Regency. The research sample was class VIII students of SMP Negeri 5 Tompobulu, Gowa Regency, totaling 28 students, with a total sampling technique. The data collection technique in this study was a test technique. The data obtained were analyzed through several stages, namely: (1) compiling raw scores, (2) frequency distribution, (3) calculate the students average score, (4) classifying the level of student ability based on the minimum completeness criteria (KKM). The results of the study showed that the ability to write Makassar language conversation texts was still relatively low. Of the 28 students, 9 students (32.2%) were in the capable category, while 19 students (67.8%) were in the unable category. Thus, it can be concluded that the ability to write Makassar language conversation texts of class VIII students of SMP Negeri 5 Tompobulu, Gowa Regency as a whole is in the unable category